Beneficial effects of rapamycin on endothelial function in systemic lupus erythematosus - Kim, Hyoseon; Massett, Michael P. (Frontiers in Physiology, 2024)
Endothelial function is significantly impaired in patients with SLE compared to healthy controls. Elevated activation of the mechanistic target of rapamycin complex 1 (mTORC1) is reported in humans and mice with SLE. However, it is unclear if elevated mTORC1 in SLE contributes to impaired mitophagy and endothelial dysfunction. Therefore, we tested the hypothesis that inhibiting mTORC1 with rapamycin would increase mitophagy and attenuate endothelial dysfunction and inflammatory responses in SLE. Nine-week-old female lupus-prone (MRL/lpr) and healthy control (MRL/MpJ) mice were randomly assigned into rapamycin treatment (lpr_Rapamycin and MpJ_Rapamycin) or control (lpr_Control and MpJ_Control) groups. Rapamycin was injected i.p. three days per week for 8 weeks. After 8 weeks, endothelium-dependent vasorelaxation to acetylcholine (Ach) and endotheliumindependent vasorelaxation to sodium nitroprusside (SNP) were measured in thoracic aortas using a wire myograph. MTORC1 activity was increased in aorta from lpr mice as demonstrated by increased phosphorylation of s6rp and p70s6k and significantly inhibited by rapamycin (s6rp, p < 0.0001, p70s6k, p = 0.04, respectively). Maximal responses to Ach were significantly impaired in lpr_Control (51.7 ± 6.6%) compared to MpJ_Control (86.7 ± 3.6%) (p<0.0001). Rapamycin prevented endothelial dysfunction in the thoracic aorta from lupus mice (lpr_Rapamycin) (79.6 ± 4.2%) compared to lpr_Control (p = 0.002). Maximal responses to SNP were not different across groups. Phosphorylation of endothelial nitric oxide synthase also was 42% lower in lpr_Control than MpJ_Control and 46% higher in lpr_Rapamycin than lpr_Control. The inflammatory marker, vascular cell adhesion protein 1 (Vcam 1), was elevated in aorta from lupus mice compared with healthy mice (p = 0.001), and significantly reduced with Rapamycin treatment (p = 0.0021). Mitophagy markers were higher in lupus mice and reduced by rapamycin treatment, suggesting altered mitophagy in lpr mice. Collectively, these results demonstrate the beneficial effects of inhibiting mTORC1 on endothelial function in SLE mice and suggest inflammation and altered mitophagy contribute to endothelial dysfunction in SLE.